2004
DOI: 10.1038/sj.gene.6364114
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a disease susceptibility locus in chromosome 6p in Japanese patients with ulcerative colitis

Abstract: Ulcerative colitis (UC) is a multifactorial disorder with both genetic and environmental factors. HLA-B*52 and DRB1*1502 are reported to be strongly associated with UC in Japan. However, the actual susceptible gene has not been identified yet. In this study, to map precisely the susceptible locus for UC, we performed association mapping in the chromosome 6p using 24 microsatellite markers distributed over 16 Mb. A total of 183 patients with UC and 186 healthy controls (HC) were included in this study. In all, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In Japan, according to Nomura et al. , important determinants of disease susceptibility to UC may exist in HLA, especially the centromeric region of Class III, under a strong linkage disequilibrium with HLA‐B (*)52 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Japan, according to Nomura et al. , important determinants of disease susceptibility to UC may exist in HLA, especially the centromeric region of Class III, under a strong linkage disequilibrium with HLA‐B (*)52 6 …”
Section: Discussionmentioning
confidence: 99%
“…In Japan, according to Nomura et al, important determinants of disease susceptibility to UC may exist in HLA, especially the centromeric region of Class III, under a strong linkage disequilibrium with HLA-B (*)52. 6 In the UK, Ahmad et al identified HLA-DRB1 alleles (DRB1*0103, DRB1*1502 and DRB1*0401) as having the strongest association with overall susceptibility. 7 In Spain, Fdez-Morera et al investigated the possible association of HLA-B, HLA-DR and HLA Class I chain-relatedtransmembrane (MICA-TM) polymorphisms with the behavior and extension of UC.…”
Section: Discussionmentioning
confidence: 99%
“…An approach for association analysis was performed as previously reported 8 . Briefly, allele and carrier frequencies (proportion possessing one or two copies of an allele) were estimated by direct counting.…”
Section: Methodsmentioning
confidence: 99%
“…We have previously reported the presence of a disease susceptible locus within that area in patients with inflammatory bowel diseases such as ulcerative colitis (UC) and Crohn disease (CD). 7,8 The Japanese population has an advan-© 2007 The Japan Society of Hepatology tage in that these is less heterogeneity in the population than is seen in the Caucasoid race living in Europe, and the Japanese are also thought to be suitable for association analysis due to the country's geographic condition. 9 However, no linkage disequilibrium mapping (LDM) analyses about PBC have been reported in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Linkage studies have clearly established that this region contributes to IBD pathogenesis (both CD and UC). Linkage has been consistently replicated across different populations, which may suggest that there are several susceptibility factors in the extended MHC [24,25,94] . Calculations derived from studies of HLA allele sharing within families suggest that this region contributes between 10 and 33% of the total genetic risk of CD and 65 and 100% of the total genetic risk of UC [95,96] .…”
Section: Ibd3/chromosomementioning
confidence: 95%